Milníky kardiovaskulární terapie. V. Diuretika - Jerie, P (Casopis lekaru ceskych, 2007)
After their introduction in 1959, thiazide diuretics have become the cornerstone in the managment of heart failure and hypertension. They prevent sodium reabsorption in the upper segment of the distal tubule, increase the diuresis and, by diminishing the intravascular volume, they reduce the preload. With vigorous diuresis, cardiac output may drop under the critical level, and hypovolaemia, hypotension, syncopes and dehydratation with severe water-mineral disturbance may occur. A similar disorder takes place after aggressive administration of loop diuretics which act by the same mechanism at the ascending limb of the loop of Henle. Moreover, any chronic treatment with saluretics triggers the contraregulatory activation of RAAS. Thus, the dosing should be cautiously titrated, and with diminishing efficacy the diuretic is to be replaced by another one, or a second drug is to be added. With any potent diuretic agent, electrolyte depletion may occur; therefore, minimal active doses should be applied, potassium-sparing diuretics added or a pause should be inserted after/before furosemide with spirolactone. Hyponatraemia and hypokalaemia are common, and in combined treatment with ACE-inhibitors and spirolactone, hyperkalaemia is frequent. With long-term treatment, a rebound period of sodium reabsorption follows, and the diuretic effect is reduced or lost. To overcome this ",diuretic resistance", the dietary sodium is to be restricted, physical effort avoided and salt retaining drugs (NSAIDs and similar) eliminated. In the article, a short review of basic physiology concerning the water-electrolyte balance and the distribution of body-water is summarized.
Keywords: Antihypertensive Agents; Hypertension; hypertenze; lidé; antihypertenziva; Heart Failure; Diuretics; Humans; srdeční selhání; inhibitory symportérů pro chlorid sodný; diuretika; Sodium Chloride Symporter Inhibitors